Głos Łodzi . pismo NSZZ "Solidarność" Region Ziemi Łódzkiej, no. 37, 1986 - Solidarność Walcząca [wydawnictwo w Łodzi] ([s.n.], 1986)
Creation and circulation: W 1989 r. published legally titled Głos Solidarności